2003
DOI: 10.3928/0147-7447-20030101-14
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Medical Complications in Geriatric Patients With Hip Fracture

Abstract: The records of 510 elderly patients with hip fractures admitted to our institution between January 1995 and December 2000 were retrospectively reviewed to determine the incidence and type of developed medical complications and their economic implications. Of those 510 patients, 217 (43%) developed at least 1 medical complication, most frequently electrolyte imbalance (11%), urinary tract infection (10%), respiratory failure (10%), and delirium (9%). Patients who developed medical complications had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 99%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrate that integrated orthogeriatric treatment is associated with a reduction in hospital mortality and long-term mortality rates [43][44][45][46][47][48]. A metaanalysis including 18 studies (9094 patients) concluded that combined orthopaedic and geriatrician care reduced mortality [13].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, la determinación entre optar por la hemiartroplastía unipolar o bipolar es una consideración adicional crucial en el manejo de fracturas de cadera en personas mayores. Conforme el análisis de Khasraghi et al (2005), los pacientes sometidos a una hemiartroplastía bipolar reportaron resultados funcionales superiores y menor dolor postoperatorio en comparación con aquellos tratados con una hemiartroplastía unipolar. La selección entre estas alternativas podría depender de diversos factores, incluyendo la expectativa de vida del paciente, el grado de actividad física y la calidad ósea.…”
Section: Discussionunclassified